Effects of Moringa oleifera Leaf Extract on Liver Histopathology: A Systematic Review - Titing Nurhayati; Muhamad Farrel Ridho; Putri Teesa Radhiyanti Santoso; Setiawan Setiawan; Hanna Goenawan; Vita Murniati Tarawan (Journal of Nutrition and Metabolism)
Introduction. Moringa leaves (Moringa oleifera), which are members of the Moringaceae family, are one of the herbal plants that are widely known in Indonesia. Phytochemical contents of moringa leaf, such as flavonoid, quercetin, and phenolic acid, are believed to have an effect on improvement of NAFLD. Therefore, moringa leaf is considered as one the herbal plants that can be used as supplementation in the form of adjuvant therapy to NAFLD. The study objective of our research is to review the effect of giving moringa leaf to the liver, especially the histopathologic features. This study will be conducted on literature review research design, more specifically in the form of a systematic review. Research Method. Five major electronic web databases, including PubMed, Cochrane Library, Google Scholar, Scopus, and ScienceDirect, were used in identifying literature from 2014 to 2023. Results. From a comprehensive analysis of 13 relevant literature sources, we elucidate the impact of Moringa oleifera leaf extract on liver histopathology, glucose, and lipid metabolism. Furthermore, we provide insights into its safety profile concerning human health. Conclusion. The phytochemical content of Moringa oleifera leaf extract had shown a significant benefit in plant medicinal sector. From the research that had been done, Moringa oleifera leaf extract contributes to give significant improvement on liver histopathological features, glucose, and lipid metabolism on animal sample model.